2009
DOI: 10.1111/j.1469-7610.2009.02083.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression and mother–child interaction patterns: association with toddler problems and continuity of effects to late childhood

Abstract: In sum, these findings suggest that for mothers with high levels of depressive symptoms, demonstrations of affection and responsiveness to toddler offspring may mitigate both current and long-term consequences on offspring behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
51
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 37 publications
8
51
0
4
Order By: Relevance
“…Nonetheless, there is also evidence that complex bidirectional relationships exist between maternal and offspring characteristics and, for example, that offspring temperament and personality influence how mothers perceive their children and react to them [42][43][44][45][46]. Furthermore, research found the association between an unfavorable family environment and offspring psychopathology to be pronounced in the presence of parental psychopathology [14,[47][48][49][50][51][52]. For instance, parental social phobia interacted with parenting on predicting offspring social phobia in a way that unfavorable parenting was more strongly associated with offspring social phobia in the presence of parental social phobia [14].…”
Section: Introductionmentioning
confidence: 91%
“…Nonetheless, there is also evidence that complex bidirectional relationships exist between maternal and offspring characteristics and, for example, that offspring temperament and personality influence how mothers perceive their children and react to them [42][43][44][45][46]. Furthermore, research found the association between an unfavorable family environment and offspring psychopathology to be pronounced in the presence of parental psychopathology [14,[47][48][49][50][51][52]. For instance, parental social phobia interacted with parenting on predicting offspring social phobia in a way that unfavorable parenting was more strongly associated with offspring social phobia in the presence of parental social phobia [14].…”
Section: Introductionmentioning
confidence: 91%
“…We explored whether these disorders arose in mothers after the birth of a child who was difficult to manage, but found no clear evidence of a relationship between onset of mothers' mental disorders and birth of probands. This suggests a possible nonspecific relationship between maternal anxious psychopathology and offspring mood dysregulation (Leckman-Westin et al 2009). Maternal psychopathology has been shown to impact mothers' reporting of their child's difficulties (Briggs-Gowan et al 1996); such a bias cannot be ruled out in the current study.…”
Section: Features Of Children With Outburstsmentioning
confidence: 99%
“…특히, 주 양육자의 심리·정서는 삶의 만족도와 밀접한 관련이 있는 것으로 나타나 스스로의 삶에 대하여 만족하지 못하면 우울 등의 부정적인 감정을 함양하게 되는데 (조준오, 나정, 홍광 표, 2015) 주 양육자의 불안정한 감정들은 자녀의 정신건강을 저해하는 것으로 나타났다 (Cummings, Keller, & Davies, 2005;Leckman-Westin, Cohen, & Stueve, 2009). 즉, 부모의 불안정한 심리상태는 아동에게 감정적인 학대에 주된 원인이 되어 부정적인 정서와 부적절한 행동문제에 원인이 되므로 (Brook & Schmidt, 2008;Leckman-Westin et al, 2009;Olfson, Marcus, Pincus, & Weissman, 2003) 이들의 우울을 더욱 가중시킬 수 있다.…”
unclassified
“…즉, 부모의 불안정한 심리상태는 아동에게 감정적인 학대에 주된 원인이 되어 부정적인 정서와 부적절한 행동문제에 원인이 되므로 (Brook & Schmidt, 2008;Leckman-Westin et al, 2009;Olfson, Marcus, Pincus, & Weissman, 2003) 이들의 우울을 더욱 가중시킬 수 있다. 이러한 맥락에서 볼 때, 주 양육자의 삶 의 질은 자녀의 정신건강 간의 상관이 있을 것으로 예측된다.…”
unclassified